Psychopathic personality factor "Fearless dominance" is related to low self-reported stress-levels, fewer psychiatric symptoms, and more adaptive stress coping in psychiatric disorders. (December 2018) - Dalkner, Nina; Reininghaus, Eva Z.; Riedrich, Karin; Rieger, Alexandra; Birner, Armin; Fellendorf, Frederike T.; Bengesser, Susanne A.; Queissner, Robert; Platzer, Martina; Mayr-Mauhart, Markus; Dorn, Matthias; Reininghaus, Bernd
Highlights: Previous studies suggest altered stress response in psychopaths; however no study investigated stress coping mechanisms regarding the degree of different psychopathic factors (Fearless dominance versus Self-centered impulsivity) in a large psychiatric sample. Structural equation modeling showed that higher levels in the psychopathic trait Fearless dominance have a direct effect on psychiatric symptoms, chronic stress experience and adaptive coping strategies. Fearless dominance was negatively related to self-reported stress symptoms and positively to adaptive coping strategies - to decrease stress (e.g. Play down). Psychopathic features – especially Stress Immunity, Social Influence - may serve as buffer against psychological stress and depressive symptoms. Abstract: The aim of this cross-sectional study was to test the idea that the psychopathic trait "Fearless dominance" (FD) may be associated with reduced psychological stress symptoms and better stress coping strategies in psychiatric patients, whereas the factor "Self-centered impulsivity" (SCI) may be associated with more stress and maladaptive stress coping. The investigation included 626 individuals with psychiatric disorders treated in a psychiatric rehabilitation program. The participants were tested with the Psychopathic Personality Inventory Revised (PPI-R) and completed several clinical scales measuring stress experience and stress coping (Symptom-Checklist Revised, Trier Inventory for Chronic Stress, The Stress Coping Style Questionnaire 78). Consistent with the hypothesis, structural equation modeling results showed that self-reported stress levels and adaptive stress coping strategies might be explained by psychopathic FD traits in the psychiatric sample. Supplemental subscale analyses showed that especially the PPI-R scales Stress Immunity and Social Influence were positively related to adaptive stress coping. The second model of SCI did not fit our data well. In conclusion, individuals with psychopathic FD traits may experience less stress symptoms during residential care. Well-designed prospective trials may ultimately answer the question whether psychopathic traits could be viewed as serving a buffer function in the development of depression.